2008
DOI: 10.1007/s11845-008-0187-2
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of text message reminders on non-attendance at outpatient clinics

Abstract: The rate of non-attendance is 17%. A reminder would eradicate more than half of non-attendance, allowing significantly more new patients to be seen, translating to more efficient use of clinic time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…In a survey of patients who had failed to attend a general surgical outpatient clinic appointment, Hogan et al 20 report that a 'text message reminder would have encouraged 51% (n = 49) to have either attended the appointment or contacted the hospital to cancel'. However, the way that SMS reminders are delivered varied across studies, hence influencing the way that they are used to cancel or reschedule.…”
Section: Findings From Other Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…In a survey of patients who had failed to attend a general surgical outpatient clinic appointment, Hogan et al 20 report that a 'text message reminder would have encouraged 51% (n = 49) to have either attended the appointment or contacted the hospital to cancel'. However, the way that SMS reminders are delivered varied across studies, hence influencing the way that they are used to cancel or reschedule.…”
Section: Findings From Other Studiesmentioning
confidence: 99%
“…20,[111][112][113][114] Studies also suggest that health-care professionals perceive forgetfulness to be one of the most important reasons for non-attendance. 104 However, the evidence from multiple studies indicates that forgetting to attend accounted for between 8% 112 and 45% of the patients who did not attend their appointments, 74 suggesting that other factors are also in operation in many settings.…”
Section: Reported Reasons For Non-attendancementioning
confidence: 99%
See 2 more Smart Citations
“…
Dear Editor, We read with interest the publication by Hogan AM et al [1], which looked at the potential impact of text message reminders on non-attendance at surgical outpatient (OPD) clinics in Ireland and reported that such a service would encourage 51% to attend or cancel their missed OPD appointment. As the authors pointed out, little work has been carried out in this area in Ireland.
…”
mentioning
confidence: 99%